The Jews of summer: summer camp and Jewish culture in postwar America - Fox, Sandra (Stanford studies in Jewish history and culture, 2023)
Introduction : the Jewish camp : between fantasy and reality -- "Under optimum conditions" : American Jews and the rise of the summer camp -- A matter of time : constructing time for "creative survival" -- Jews playing games : role-play, sociodrama, and color war -- "A little suffering goes a long way" : Tisha B'Av, Ghetto Day, and the shadow of the Holocaust -- The language cure : embracing and evolving Yiddishism and Hebraism -- "Is this what you call being free?" : power and youth culture in the camper republic -- Summer flings and fuzzy rings : camper romance, erotic Zionism, and intermarriage anxiety -- Jewish camping post-postwar.